Episodic memory isn't essentially autonoetic. (22nd January 2018) - Carruthers, Peter
Abstract: I argue that the function attributed to episodic memory by Mahr & Csibra (M&C) – that is, grounding one's claims to epistemic authority over past events – fails to support the essentially autonoetic character of such memories. I suggest, in contrast, that episodic event memories are sometimes purely first order, sometimes autonoetic, depending on relevance in the context.